(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article provides a philosophical analysis of the causes of social problems today in relation to the life of the individual and society. It is written about the interactions and relationships between people and the qualities and external social influences that belong to the individual, and then his activity as a subject of these influences